Liability of foreignness, natural disasters, and corporate philanthropy - Mithani, Murad A (Journal of International Business Studies, 2017)
This study examines how philanthropy can mitigate liability of foreignness (LOF) in the aftermath of a national disaster. A major disaster restructures the social landscape, creating an avenue for corporate contributions to play a role in recovery and relief efforts. This social restructuring offers a valuable opportunity for multinational enterprises (MNEs) to establish strong local ties. In turn, MNE contributions at such times have a stronger impact on their local acceptance. Thus, MNEs can use these events to strengthen their position in the community and mitigate LOF. Using the context of a national disaster in India, I test these arguments with a sample of 190 MNEs and 660 domestic firms. I found that in the aftermath of the disaster, the increase in MNE contributions was much larger and less strongly tied to promotional activities than the increase in contributions from domestic firms, and this difference persisted over time. Moreover, the performance implication of post-disaster philanthropy was stronger for MNEs than for domestic firms. These findings suggest that philanthropy plays a more strategic role for MNEs in the aftermath of a disaster and it has a pronounced effect on mitigating LOF.